There Is No Such Thing as an African Value of Dependence & What Is the Matter with Values?: A Reply to Joel Robbins & A Response to Lockwood. - Lockwood, Peter; Robbins, Joel (Social Analysis, 2025)
In "Anthropology Bright and Dark," Joel Robbins encourages anthropologists to identify "visions of the good" and to explore whether they enable or inhibit "human flourishing." Ethnographic work on dependence in southern Africa informs his approach and provides a key example of a "model of the good life" in which patron-client relations are seen as ideal social arrangements. But by locating visions of the good in culture, Robbins's approach obscures questions of history, agency, and political economy. The consequence is a misreading of the economic conditions in Africa under which dependent social relationships are sought. Instead of isolating visions of the good, this reply argues that anthropology must reclaim its original holism—its capacity to create synthetic accounts of history, political economy, and moral thought.